Catalytic asymmetric synthesis of biologically important 3-hydroxyoxindoles: an update - Yu, Bin; Xing, Hui; Yu, De-Quan; Liu, Hong-Min (Beilstein Journal of Organic Chemistry, 2016)
Oxindole scaffolds are prevalent in natural products and have been recognized as privileged substructures in new drug discovery. Several oxindole-containing compounds have advanced into clinical trials for the treatment of different diseases. Among these compounds, enantioenriched 3-hydroxyoxindole scaffolds also exist in natural products and have proven to possess promising biological activities. A large number of catalytic asymmetric strategies toward the construction of 3-hydroxyoxindoles based on transition metal catalysis and organocatalysis have been reported in the last decades. Additionally, 3-hydroxyoxindoles as versatile precursors have also been used in the total synthesis of natural products and for constructing structurally novel scaffolds. In this review, we aim to provide an overview about the catalytic asymmetric synthesis of biologically important 3-substituted 3-hydroxyoxindoles and 3-hydroxyoxindole-based further transformations.
Keywords: 3-hydroxyoxindoles; oxindoles; organocatalysis; spirooxindoles; transition metal catalysis